Implementing the INTERGROWTH‐21st fetal growth standards in France: a 'flash study' of the College Français d'Echographie Foetale (CFEF). (April 2017) - Stirnemann, J. J.; Fries, N.; Bessis, R.; Fontanges, M.; Mangione, R.; Salomon, L. J.
ABSTRACT: Objectives: To assess potential differences in fetal size between the French population and the international population from the INTERGROWTH‐21 st (IG‐21 st ) Project and to measure the impact of switching to the IG‐21 st reference standards for fetal size. Methods: This was a nationwide cross‐sectional study of fetal ultrasound biometry. Low‐risk singleton pregnancies were recruited prospectively within the network of the national French College of Fetal Ultrasound, CFEF, over a 6‐week period. Further selection was performed based on the criteria of the IG‐21 st Project in order to obtain a comparable population. Head circumference (HC) was used as the main fat‐free skeletal measure of growth for comparison of French fetal size with that of the IG‐21 st population. The impact of switching to the IG‐21 st fetal growth standards was quantified by comparing Z ‐scores calculated using the IG‐21 st standards with those calculated using locally derived reference ranges for HC, abdominal circumference (AC) and femur length (FL). Results: Following selection, 4858 cases were analyzed. The distribution of HC demonstrated clear similarity between our French population and the IG‐21 st population: our observed centile curves closely matched those of IG‐21 st and the Z ‐scores were close to 0 across gestational age. The IG‐21 st standards performed as well as did locally derived charts in terms of screening for small‐for‐gestational age by AC, while they identified significantly fewer small FL values than were expected and than did the locally derived charts. Conclusions: Under strict selection criteria, fetal size in France is similar to that of the international population used in the IG‐21 st Project. The discrepancies in FL are unlikely to impact on prenatal management. Therefore, switching from locally derived reference ranges to the IG‐21 st standards appears to be a safe option. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.